Revolutionizing English Vocabulary Learning for Malaysian University Students through Gamified Mobile Learning (International Journal of Innovative Computing, 2024)
Low vocabulary knowledge remains a significant challenge for Malaysian university students during their English learning journey. The traditional method of memorizing English vocabulary often feels tedious and lacks inspiration. However, the education landscape is evolving rapidly with technological advancements. Mobile learning (M-Learning) has emerged as a transformative approach, enabling students to engage with English language learning through mobile platforms, especially on smartphones. One innovative trend in education that holds great promise is the integration of gamification. This approach seeks to enhance students' motivation and active participation in the learning process. This study introduces a gamification approach to address the vocabulary challenge faced by Malaysian university students—the "EasyLearn" application. This Android-based solution leverages the power of gamification to assist Malaysian university students in acquiring English vocabulary. Employing an iterative development model, this study focuses on the gamification approach's implementation. Three iterations encompassing requirement and analysis, design, implementation, and testing were conducted. EasyLearn application was successfully deployed and aligning seamlessly with user requirements. By emphasizing gamification in English language learning, this pioneering mobile learning solution represents a significant step forward in fostering motivation and enthusiasm among Malaysian university students, ultimately transforming the way they approach vocabulary acquisition.
Keywords: Gamification, mobile application, English vocabulary learning, mobile learning, M-learning